The core/penumbra model: implications for acute stroke treatment and patient selection in 2021 - Baron, Jean‐Claude (European journal of neurology, 2021)
Despite major advances in prevention, ischaemic stroke remains one of the leading causes of death and disability worldwide. After centuries of nihilism and decades of failed neuroprotection trials, the discovery, initially in non‐human primates and subsequently in man, that ischaemic brain tissue termed the ischaemic penumbra can be salvaged from infarction up to and perhaps beyond 24 h after stroke onset has underpinned the development of highly efficient reperfusion therapies, namely intravenous thrombolysis and endovascular thrombectomy, which have revolutionized the management of the acute stroke patient. Animal experiments have documented that how long the penumbra can survive depends not only on time elapsed since arterial occlusion (‘time is brain’), but also on how severely perfusion is reduced. Novel imaging techniques allowing the penumbra and the already irreversibly damaged core in the individual subject to be mapped have documented that the time course of core growth at the expense of the penumbra widely differs from patient to patient, and hence that individual physiology should be considered in addition to time since stroke onset for decision‐making. This concept has been implemented to optimize patient selection in pivotal trials of reperfusion therapies beyond 3 h after stroke onset and is now routinely applied in clinical practice, using computed tomography or magnetic resonance imaging. The notion that, in order to be both efficient and harmless, treatment should be tailored to each patient's physiological characteristics represents a radical move towards precision medicine. After centuries of nihilism and decades of failed neuroprotection trials, the discovery initially in non‐human primates and subsequently in man, that ischemic brain tissue termed the ischemic penumbra can be salvaged from infarction up to and perhaps beyond 24hrs after stroke onset. This has underpinned the development of highly efficient reperfusion therapies, namely intravenous thrombolysis and endovascular thrombectomy, which have revolutionized the management of the acute stroke patient. Novel imaging techniques that allow to map the penumbra and the already irreversibly damaged core in the individual subject have documented the response to reperfusion therapies, as illustrated in these two similar patients, one (top row) with successful salvage of the penumbra following effective recanalization, and the other (bottom row) the opposite outcome.